From Conventional to Cutting-edge: A Comprehensive Review on Drug Delivery Systems - Vikal, Akash; Maurya, Rashmi; Bhowmik, Shuvadip; Patel, Preeti; Gupta, Ghanshyam D.; Kurmi, Balak Das (Drug Delivery Letters, 2024)
The essential need for efficacious conveyance of therapeutics to specific tissues or cells, refinement of drug formulations, and the scalability of industrial production drives the present- day demand for enhanced drug delivery systems (DDS). Newly devised drugs often exhibit suboptimal biopharmaceutical properties, resulting in diminished patient adherence and adverse side effects. The paramount importance of site-specific drug delivery lies in its capacity to facilitate the targeted administration of diverse therapeutic agents, catering to both localized ailments and systemic treatments. Alongside targeted drug delivery strategies encompassing ligand-based targeting and stimuli-responsive systems, the advent of cutting-edge nanotechnologies such as nanoparticles, liposomes, and micelles has marked a paradigm shift. Additionally, personalized medicines have emerged as a consequential facet of drug delivery, emphasizing the customization of treatment approaches. Researchers have explored an excess of methodologies in the advancement of these formulation technologies, including stimuli-responsive drug delivery, 3D printing, gene delivery, and various other innovative approaches. This comprehensive review aims to provide a holistic understanding of the past, present, and future of drug delivery systems, offering insights into the transformative potential of emerging technologies.
Keywords: nanotechnology